The effect of rehabilitative exercises accompanying reflexology massage in the treatment of shoulder injury for young handball players (Texas Journal of Multidisciplinary Studies, 2022)
The research aims to prepare rehabilitative exercises accompanying massage with reflexology points to rehabilitate the shoulder joint after a dislocation injury, and the experimental design with one group with two pre and post tests was used on a sample of (12) players with a dislocated shoulder joint. After conducting the tribal tests, they were subjected to qualifying exercises, and before each qualifying unit, the player was subjected to reflexology for a period ranging from (5-10) minutes, and the duration of the qualifying units took 12 weeks at 36 units, and after completing the qualifying program, the post-tests were conducted. The most important results were that there are statistically significant differences between the pre and post test in the range of motion on the shoulder joint in favor of the post test, and there are statistically significant differences between the pre and post test in the degree of pain in the shoulder joint in favor of the post test. The most important recommendations were to use the proposed rehabilitation program to rehabilitate the dislocated shoulder injury for athletes to avoid the injury happening again, to use rubber rope exercises to rehabilitate the range of motion and to improve the neuromuscular response. The use of static muscle strength exercises and various flexibility exercises for the affected limb in the program with the use of reflexology points massage before each rehabilitation unit to reduce the feeling of pain .